Weather, Mood and Stock Market Returns in Argentina - Bakri, Abdul Karim; Muhammad Hafiz, Mohd Shukri; Tay, Sharon Chyu Yuin (Sciedu Press, 2018)
The paper examines the relationship between weather and stock market returns in the Argentina’s stock market using daily data from 2001 to 2014 and regression models. The data consists of stock market returns, temperature, humidity and wind. The empirical findings show that all weather variables (temperature, humidity and wind) have significant relationship with stock market returns in some of the trading days in the week. We also find evidence of the existence of day-of-week effect in the stock market. On average, the highest return falls on Friday and lowest return falls on Monday. Temperature is considered very significant in influencing the stock market returns in Argentina. Our findings suggest that the stock market returns are higher when the temperature is higher. This phenomenon is related to the seasonal affective disorder (SAD). We can conclude that stock market of Argentina is not informational efficient. The results have major implications for traders, individual investors, fund managers and financial institutions to make investment planning in the Argentina’s stock market.